An explanatory model for academic stress: accounting for loneliness, social support, perfectionism, and help-seeking attitudes in a Latino college sample (2026)
This study aimed to analyze the influence that perfectionism, mental help-seeking attitudes (MHSA), social support, and loneliness have over academic stress on a college sample using a multiple linear regression, a descriptive cross-sectional design was utilized. There were 623 participants (218 Colombian and 405 American participants) with an average age of 22 (M= 22.6, SD=3.08), the instruments employed were the frost multidimensional perfectionism scale (FMP), SISCO, multidimensional perceived social support scale, the UCLA loneliness scale and the mental help-seeking attitudes scale. Results show that American students have greater perfectionistic traits, while Colombian show higher loneliness, social support, and academic stress. Additionally, the correlation analysis produced similar results across both samples, indicating that the dependent variable was positively correlated with perfectionism and loneliness, while it was negatively correlated with social support and MHSA. Moreover, an adjusted R 2=0.28 was found, where three perfectionism subscales, loneliness, perceived social support, and MHSA explain 28% of the variance in academic stress. The variables that contributed the most to the model were the perfectionism subscales and loneliness.